Cultural Identity and Special Education Teachers: Have We Slept Away Our Ethical Responsibilities? - Salas, Loretta; López, Eric J. (Journal of the American Academy of Special Education Professionals, 2008)
All teachers play a pivotal role, if not the most important role, in the success or failure of culturally and linguistically diverse children, but most importantly in the field of special education as overrepresentation of these children continues to grow. We believe that those teachers who are aware of their own ethnic identity are better prepared to work with children from culturally and linguistically diverse backgrounds. Consequently, it is our contention that the knowing of one’s ethnic identity is an ethical issue for special education teachers as they attempt to understand the lives of those children who differ from themselves. This paper explores the notion of cultural and ethnic identity and its relationship to the special education teacher.